Blending chitosan‐g‐poly(caprolactone) with poly(caprolactone) by electrospinning to produce functional fiber mats for tissue engineering applications. Issue 18 (1st November 2019) - de Cassan, Dominik; Becker, Alexander; Glasmacher, Birgit; Roger, Yvonne; Hoffmann, Andrea; Gengenbach, Thomas R.; Easton, Christopher D.; Hänsch, Robert; Menzel, Henning
ABSTRACT: Use of electrospun fiber mats for tissue engineering applications has become increasingly prominent. One of the most important polymers in research, poly(ε‐caprolactone) (PCL), however, lacks biological performance, easy access to modifications and cellular recognition sites. To improve these properties and to enable further modifications, PCL was blended with chitosan grafted with PCL (CS‐g‐PCL) and subsequently processed via electrospinning. In this way, chitosan was enriched at the fiber's surface presenting cationic amino groups. The fiber mats were analyzed by various techniques such as scanning electron microscopy (SEM), confocal laser scanning microscopy (CLSM), and X‐ray photoelectron spectroscopy (XPS). Furthermore, analyzing thermal properties and crystallinity, showed that an increased content of CS‐g‐PCL in blend composition leads to a higher overall crystallinity in produced fiber mats. Blending CS‐g‐PCL into PCL significantly increased initial cellular attachment and proliferation as well as cell vitality, while maintaining adequate mechanical properties, fiber diameter, and interstitial volume. As proof of principle for easy access to further modification, fluorescently labeled alginate (Alg‐FA) was attached to the fiber's surface and verified by CLSM. Hence, blending CS‐g‐PCL with PCL can overcome an inherent weakness of PCL and create bioactive implants for tissue engineering applications. © 2019 The Authors. Journal of Applied Polymer Science published by Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48650. Abstract :